« Changement » et « innovation » : Essai d’intégration théorique au cœur d’un programme de recherche mené en anthropologie culturaliste - Jérôme Amathieu; Sébastien Chaliès (Éducation et Socialisation)
This article attempts to question the possible theoretical integration of the concepts of "innovation" and "change" within the framework of a research program conducted in cultural anthropology and mainly inspired by the analytical philosophy of Wittgenstein (2004). By return, he studies the heuristic character of this integration from the point of view of the development of the research program. The article is structured around three parts. In the first part, the different levels of integration of the concepts of "change" and "innovation" within the program are explained. In the second part, an empirical illustration of this integration is proposed. Finally, in the last part, a discussion is carried out around the work of conceptual hybridization carried out and the precautions to envisage so that it is scientifically valid.